Environmental concerns and sustainable development : some perspectives from India - Somayaji, Sakarama; Somayaji, Ganesha; Tata Energy Research Institute (New Delhi : The Energy and Resources Institute, 2009)
Contributed articles.
Includes bibliographical references.
Keywords: Sustainable development -- India; Environmental degradation -- India; Environmental policy -- India